2019
DOI: 10.1042/bsr20190679
|View full text |Cite
|
Sign up to set email alerts
|

BTXA regulates the epithelial–mesenchymal transition and autophagy of keloid fibroblasts via modulating miR-1587/miR-2392 targeted ZEB2

Abstract: Keloids are very resistant to treatment in dermatology and plastic surgical practice. The present study aimed to explore the underlying mechanism of botulinum toxin A (BTXA) treated human skin keloid fibroblasts (HSFBs) proving some new insights into keloids treatment. Expression of miR-1587 and miR-2392 were significantly down-regulated in keloid tissues and HSFBs, while the ZEB2 was a target of both and up-regulated in keloid tissues and HSFBs compared with the normal controls. BTXA could significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Glioma‐associated mesenchymal stem cell‐derived exosomal miR‐1587 contributes to the tumorigenicity (Figueroa et al, 2017). miR‐1587 targets ZEB2 to regulate cell proliferation, migration, apoptosis, and autophagy in keloid fibroblasts (Hou et al, 2019). In this study, we found that breast cancer cells treated by the supernatant medium of M2 macrophage showed a high level of miR‐1587, and miR‐1587 overexpression contributes to cell proliferation and migration of breast cancer cells, indicating that miR‐1587 mediates TAMs function, consistent with a previous report exosomes enriched miR‐1587 mediates glioma progression (Figueroa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Glioma‐associated mesenchymal stem cell‐derived exosomal miR‐1587 contributes to the tumorigenicity (Figueroa et al, 2017). miR‐1587 targets ZEB2 to regulate cell proliferation, migration, apoptosis, and autophagy in keloid fibroblasts (Hou et al, 2019). In this study, we found that breast cancer cells treated by the supernatant medium of M2 macrophage showed a high level of miR‐1587, and miR‐1587 overexpression contributes to cell proliferation and migration of breast cancer cells, indicating that miR‐1587 mediates TAMs function, consistent with a previous report exosomes enriched miR‐1587 mediates glioma progression (Figueroa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-2392 and miR-1587 were found to target the ZEB2 protein, a promoter of the epithelial-mesenchymal transition. A lower expression of these two miRNAs were found in human keloid tissues that resulted in a loss of inhibition of ZEB2 and subsequent promotion of cellular proliferation and invasion in keloids (Hou et al, 2019). Inhibition of miR-2392 by the long-non-coding RNA CACNA1G-AS1 was found to promote hepatocellular carcinoma through disrupting the degradation of C1orf61, a tumor activator associated with metastasis and tumor progression (Hu et al, 2013;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of miR-2392 by the long-non-coding RNA CACNA1G-AS1 was found to promote hepatocellular carcinoma through disrupting the degradation of C1orf61, a tumor activator associated with metastasis and tumor progression (Hu et al, 2013;Yang et al, 2019). Recently, Fan et al demonstrated a novel role for miR-2392 in the regulation of chemoresistance in tongue squamous cell carcinoma by partial inhibition of mitochondrial DNA (mtDNA) transcription through direct miRNA-mtDNA base pairing which resulted in reprogramming tumor cell metabolism (Fan et al, 2019). These reports for miR-2392 establish the significant impact this single miRNA may have in on cellular activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations